“I Will Bear Witness That I Remember”: The Novel Umschlagplatz by J.M. Rymkiewicz - Irina E. Adelgeim (Studia Litterarum)
The article analyses the novel Umschlagplatz (1988) by a significant Polish writer and literary critic, J.M. Rymkiewicz, which deals with a twice iconic space (Warsaw’s Umschlagplatz — pars pro toto of the Holocaust and the painful problem of Polish- Jewish relations during and after the Second World War). The article aims to determine the novel’s place in the ongoing debate in Polish society about Polish complicity in the Holocaust since the second half of the 1980s. The analysis of the complex text construction covers the relationship between poetics and the problem of testimony, the modality of fiction. Generated by an acute sense of the blatant non-presence of the space of the Jewish tragedy in Polish historical consciousness as a place of memory, guilt, and shame, Rymkiewicz’s novel appears as a postulate of commemoration and empathy addressed to Polish society, a call for recognition and comprehension of the traumatic past. Umschlagplatz was a significant artistic and ethical step in preparation for working through the Holocaust-related Polish trauma, complicated by the persistence of the heroic-romantic self-identification of Polish society.